Revisiting bicoid function: complete inactivation reveals an additional fundamental role in Drosophila egg geometry specification. - Baumgartner, S. (Hereditas, 2024)
The bicoid (bcd) gene in Drosophila has served as a paradigm for a morphogen in textbooks for decades. Discovered in 1986 as a mutation affecting anterior development in the embryo, its expression pattern as a protein gradient later confirmed the prediction from transplantation experiments. These experiments suggested that the protein fulfills the criteria of a true morphogen, with the existence of a homeodomain crucial for activation of genes along the anterior-posterior axis, based on the concentration of the morphogen. The bcd gene undergoes alternative splicing, resulting in, among other isoforms, a small and often neglected isoform with low abundance, which lacks the homeodomain, termed small bicoid (smbcd). Most importantly, all known classical strong bcd alleles used in the past to determine bcd function apparently do not affect the function of this isoform. To overcome the uncertainty regarding which isoform regulates what, I removed the bcd locus entirely using CRISPR technology. bcd[CRISPR] eggs exhibited a short and round appearance. The phenotype could be ascribed to smbcd because all bcd alleles affecting the function of the major transcript, termed large bicoid (lgbcd) showed normally sized eggs. Several patterning genes for the embryo showed expression in the oocyte, and their expression patterns were altered in bcd[CRISPR] oocytes. In bcd[CRISPR] embryos, all downstream segmentation genes showed altered expression patterns, consistent with the expression patterns in "classical" alleles; however, due to the altered egg geometry resulting in fewer blastoderm nuclei, additional constraints came into play, further affecting their expression patterns. This study unveils a novel and fundamental role of bcd in shaping the egg's geometry. This discovery demands a comprehensive revision of our understanding of this important patterning gene and prompts a reevaluation of past experiments conducted under the assumption that bcd mutants were bcd[null]-mutants.